Perception Towards Memorability of Advertisements on TV-A Descriptive Study - Pongiannan, K. (Indian Journal of Marketing, 2009)
Television is often called "The King" of the advertising media, since a majority of people spends more hours in watching TV per day than any other medium. The interaction of sight and sound offers tremendous creative flexibility and makes dramatic life-like representation of products possible. TV commercials can be used to convey a mood or image for a brand as well as to develop emotional or entertaining appeals that help to make dull products appear interesting. Moreover, memorability of the advertisement and the advertised product is an important factor that may create a desire for the product, which in turn, induces to buy it. A variety of techniques are available in TV for the production of commercial messages like live action, puppet show, cartoons, documentary films and use of music, which can increase the memorability of the audience. Hence, this paper discusses about the audience's order of preference for the different TV channels, their perception and reasons for the memorability of TV advertisements in general and its impact on the various functional forms of TV advertisements